Shakespeare and the truth-teller : confronting the cynic ideal - Hershinow, David (Edinburgh : Edinburgh University Press, 2019)
Highlighting the necessity of literary thinking to political philosophy, this book explores Shakespeare's responses to sixteenth-century debates over the revolutionary potential of Cynic critical activity.
Introduction -- Part I: Our cynic legacy -- Cynicism and the courage of truth -- The realist turn: parrhêsia, character and the limits of didacticism -- Part II: Shakespeare's cynics -- Shakespeare's bitter fool: the politics and aesthetics of free speech -- Cynicism, melancholy and Hamlet's memento moriae -- Cash is king: Timon, Diogenes and the search for sovereign freedom -- Coda -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Shakespeare, William, -- 1564-1616 -- Philosophy; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616; Cynicism in literature; Realism in literature; Cynisme dans la littérature.; Réalisme dans la littérature.; LITERARY CRITICISM -- Shakespeare; Philosophy; Cynicism in literature; Realism in literature; Criticism, interpretation, etc